Penilaian Tata Kelola Teknologi Informasi Dengan Menambahkan Unsur Keamanan Menggunakan Framework Cobit 5 Pada Domain DSS - Aisyah Nuraeni; KM. Syarif Haryana (STMIK Mardira Indonesia, Bandung, 2016)
Assessment on information technology governance is a process to search for evidence of the basis of reliable, consistent and repeatable in the area of governance and management of information technology. It aims to determine the suitability of the use of technology with the business objectives of the organization. Objective is to implemtated assessment of information technology governance process by adding an element of security. The study was conducted at educational institutions using qualitative methods and frameworks COBIT 5. Domain studied were (Delivery, Support, and Service) DSS 01, DSS 02, DSS 03, DSS04, and DSS 06 by adding a subdomain DSS 05 as an element of security required. The results of the average value of domain capability by 58.61% ie largely Achieved scala rate, as for almost the entire subdomain is at level 1 and level 0 for DSS04. Keywords: assessment, IT governance, COBIT 5, security, DSS.